Morpho-biochemical diversity and phytochemical profiling of Rubus fruticosus L. landraces - Muhammad Owais; Imran Khan; Mohammad Nisar; Asghar Khan; Mohammad Ihsan; Nausheen Nazir; Farhana Ali; Muhammad Zahoor; Sumbal Khan; Shiou Yih Lee (PLoS ONE, 2026)
The flora of Khyber Pakhtunkhwa, Pakistan, is severely threatened by illegal harvesting of non-timber forest resources, resulting in the genetic loss of native plant species, including Rubus fruticosus L., a genetically diverse shrub of considerable economic and medicinal importance. The present study was designed to assess the morphological diversity, seed protein profiles, and phytochemical composition of fifteen landraces of R. fruticosus collected from different ecological zones of the Malakand Division, Khyber Pakhtunkhwa, Pakistan. Morphological characteristics were evaluated using the International Board for Plant Genetic Resources (IBPGR) descriptors, incorporating both qualitative and quantitative traits in a randomized complete block design. Seed protein diversity was assessed through sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE), while phytochemical composition was quantified using high-performance liquid chromatography with ultraviolet detection (HPLC-UV). Morphological traits exhibited significant variability, with a mean coefficient of variation (CV) of 36.72%. The most variable traits were single fruit weight (CV = 73.16%), five-fruit weight (CV = 64.38%), number of branches per plant (CV = 33.33%), plant height (CV = 31.31%), and stalk length (CV = 30.11%). Principal component analysis (PCA) explained 89.71% of the total variation, with plant height, leaflet number, and fruit weight contributing predominantly to landrace differentiation. SDS-PAGE analysis of seed proteins revealed 21 polymorphic bands (molecular weight range: 14.4–97.4 kDa), with high diversity indices recorded for markers B-03, B-06, B-08, B-12, and B-21 (Shannon diversity index H′ = 1.10–1.39; CV = 35.36–93.54%). HPLC-UV analysis identified twelve phenolic compounds in selected genotypes, including quercetin (5.12–8.74 µg/mL), morin (3.45–6.89 µg/mL), and epigallocatechin gallate (2.88–7.23 µg/mL). The morphological, biochemical, and phytochemical diversity observed among R. fruticosus landraces highlights their potential for conservation programs and future breeding initiatives.